1992
DOI: 10.1115/1.2920920
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Tilting-Pad Journal Bearings—Comparison With Theoretical Thermoelastohydrodynamic Results

Abstract: Operating characteristics of four-shoe tilting-pad journal bearings of 100 mm diameter and 70 mm length are determined on an experimental device. The load, between pad configuration, varies from 0 to 10,000 N and the rotational speed is up to 4000 rpm. Forty thermocouples are used in order to measure bearing element temperatures (babbitt, shaft, housing and oil baths). The influence of operating conditions and preload ratio on bearing performances are studied. Comparison between theoretical and experimental re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(37 citation statements)
references
References 0 publications
4
33
0
Order By: Relevance
“…The theory agreed with the Brockwell et al data within 10 percent. Theoretical results were also compared to experimental results reported by Fillon et al [61]. The effects of the TEHD model on the coefficients was shown in separate plots with synchronously reduced coefficients.…”
mentioning
confidence: 88%
“…The theory agreed with the Brockwell et al data within 10 percent. Theoretical results were also compared to experimental results reported by Fillon et al [61]. The effects of the TEHD model on the coefficients was shown in separate plots with synchronously reduced coefficients.…”
mentioning
confidence: 88%
“…In order to validate the theoretical results of our study, a comparison between experimental data and such theoretical findings will be conducted. The test bearing and other experimental data have been presented in earlier journal publications (Monmousseau et al, 1996 andFillon et al, 1992).The data of the bearing at 20°C are shown in table I. Here in these operating conditions we should mention that the shaft rotational speed is 418 9 rad/s (4000 rpm) and the static load is equal to 2000 N. In our efforts, we have found that the maximum discrepancy between experimental and theoretical results is about 5°C.…”
Section: Static Load Without Unbalance Massmentioning
confidence: 76%
“…Several thermohydrodynamic (THD) or thermoelastohydrodynamic (TEHD) analyses have been previously developed (Rohde et al1975;Khonsari et al, 1991;Fillon et al, 1990Fillon et al, , 1992Paranjpe et al 1994). Most of them are steady-state analyses.…”
Section: Introductionmentioning
confidence: 99%